Endodontic cement penetration after removal of calcium hydroxide dressing using XP-endo finisher - Alyssa Sales dos Santos; Maria Aparecida Barbosa de Sá; Marco Antônio Húngaro Duarte; Martinho Campolina Rebello Horta; Frank Ferreira Silveira; Eduardo Nunes (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: We aimed to evaluate the penetration of endodontic cement following the removal of calcium hydroxide (Ca(OH)2) dressing using the XP-endo Finisher in association with different irrigating solutions. Sixty premolars were instrumented and applied with a Ca(OH)2 dressing. To remove Ca(OH)2, the teeth were divided into six groups, each with a different volume of sodium hypochlorite (NaOCl) and ethylenediaminetetraacetic acid (EDTA), as well as solution stirring time with XP-endo Finisher (0, 30, and 60 sec). Root canals were filled using the lateral condensation technique. Fluorescein dye was added to the cement for microscopic laser scanning analysis. In the generated images, linear measurements were taken in micrometers, and their averages were calculated. To analyze the perimeter penetration ratio of the cement, the total perimeter of the canal and the segment of the total perimeter of the canal where the endodontic cement penetrated into the dentinal tubules were measured in micrometers. We found that using an XP-endo Finisher in irrigation was more effective than using a needle and syringe during the extension and penetration of endodontic cement. Shaking with XP-endo Finisher with 17% EDTA increased the extent and perimeter of the penetration of the endodontic cement into the dentinal tubules. However, using the XP-endo Finisher with EDTA only was more efficient than using the instrument interchangeably in NaOCl and EDTA. Although XP-endo Finisher contributes to the removal of Ca(OH)2, none of the protocols or instruments used removed all Ca(OH)2 from the root system.